Maternal sevoflurane exposure induces temporary defects in interkinetic nuclear migration of radial glial progenitors in the fetal cerebral cortex through the Notch signalling pathway. (6th May 2021) - Jiang, Ming; Tang, Tianxiang; Liang, Xinyue; Li, Juchen; Qiu, Yue; Liu, Shiwen; Bian, Shan; Xie, Yunli; Fang, Fang; Cang, Jing
Abstract: Objectives: The effects of general anaesthetics on fetal brain development remain elusive. Radial glial progenitors (RGPs) generate the majority of neurons in developing brains. Here, we evaluated the acute alterations in RGPs after maternal sevoflurane exposure. Methods: Pregnant mice were exposed to 2.5% sevoflurane for 6 hours on gestational day 14.5. Interkinetic nuclear migration (INM) of RGPs in the ventricular zone (VZ) of the fetal brain was evaluated by thymidine analogues labelling. Cell fate of RGP progeny was determined by immunostaining using various neural markers. The Morris water maze (MWM) was used to assess the neurocognitive behaviours of the offspring. RNA sequencing (RNA‐Seq) was performed for the potential mechanism, and the potential mechanism validated by quantitative real‐time PCR (qPCR), Western blot and rescue experiments. Furthermore, INM was examined in human embryonic stem cell (hESC)‐derived 3D cerebral organoids. Results: Maternal sevoflurane exposure induced temporary abnormities in INM, and disturbed the cell cycle progression of RGPs in both rodents and cerebral organoids without cell fate alternation. RNA‐Seq analysis, qPCR and Western blot showed that the Notch signalling pathway was a potential downstream target. Reactivation of Notch by Jag1 and NICD overexpression rescued the defects in INM. Young adult offspring showed no obvious cognitive impairments in MWM. Conclusions: Maternal sevoflurane exposure during neurogenic period temporarily induced abnormal INM of RGPs by targeting the Notch signalling pathway without inducing long‐term effects on RGP progeny cell fate or offspring cognitive behaviours. More importantly, the defects of INM in hESC‐derived cerebral organoids provide a novel insight into the effects of general anaesthesia on human brain development. Abstract : Maternal sevoflurane exposure during the neurogenic period temporarily induced abnormal INM of RGPs by targeting the Notch signalling pathway without inducing long‐term effects on RGP progeny cell fate or offspring cognitive behaviors. More importantly, the defects of INM in hESC‐derived cerebral organoids provide a novel insight into the effects of general anesthesia on human brain development.